1998
DOI: 10.1021/jf981266g
|View full text |Cite
|
Sign up to set email alerts
|

Flavonol Glycosides from the Seed Coat of a New Manteca-Type Dry Bean (Phaseolus vulgaris L.)

Abstract: In the Abstract, compound 1 should be identified as 5,7,4′-trihydroxyflavonol 3-O--D-glucopyranoside. Under Results and Discussion, the C4′ assignments were omitted; they are for kaempferol 3-O--D-glucopyranoside C4′ ) 159.92 ppm and for kaempferol 3-O--Dglucopyranoside-(2f1)--D-xylopyranoside C4′ ) 159.95 ppm. Under Literature Cited, the volume number for Kooiman (1931) is 8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 5 publications
6
40
0
1
Order By: Relevance
“…In this regard, the results agree with those of Beninger and Hosfield (1998) and Takeoka et al (1997) where both components were important to seed coat colour in common beans. This study also found that the inheritance of tannins and anthocyanins in coloured beans is predominantly quantitative with many genes involved although anthocyanin may be controlled by fewer genes related to seed colour pattern or intensity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this regard, the results agree with those of Beninger and Hosfield (1998) and Takeoka et al (1997) where both components were important to seed coat colour in common beans. This study also found that the inheritance of tannins and anthocyanins in coloured beans is predominantly quantitative with many genes involved although anthocyanin may be controlled by fewer genes related to seed colour pattern or intensity.…”
Section: Discussionsupporting
confidence: 89%
“…Tannins and anthocyanins are of simultaneous interest from a plant breeding perspective because together they influence the colour of plant organs. In bean seed, these metabolites are located mainly in the seed coat and determine the overall colour, hue and intensity of the seed (Beninger & Hosfield, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Their structures were elucidated by chemical and spectroscopic techniques (Mabry et al 1970;Agrawal & Bansal 1989;Markham & Geiger 1994), and identified as isorhamnetin-3-O-b-glucopyranoside-7-O-a-rhamnopyranoside (1), isorhamnetin-3-O-a-rhamnopyranoside-7-Ob-glucopyranoside (2), kaempferol-3,7-di-O-a-rhamnopyranoside (3), isorhamnetin-3-O-b-glucopyranoside (4), kaempferol-3-Ob-glucopyranoside (5), isorhamnetin (6) and kaempferol (7). Spectral data of the isolated flavonoids were consistent with those previously published (Beninger et al 1998;Hussein et al 2009Hussein et al , 2011Yi et al 2011).…”
Section: Identification Of Flavonoid Compoundssupporting
confidence: 90%
“…More recently, Yeo and Shahidi (2015) introduced a new indicator, the ratio of insoluble bound phenolics to soluble phenolics, and suggested it as an effective means to monitor changes in the antioxidant activity of lentils during processing as exemplified for the germination process.There are, however, only a few reports on identification and quantification of flavonoids in food legumes (Xu & Chang, 2007). For example, only several reports on common beans (Beninger, Hosfield, & Bassett, 1999;Beninger, Hosfield, & Nair, 1998;Hempel & Bohm, 1996;Madhujith, Naczk, et al, 2006;Romani et al, 2004) and peas (Troszyń ska et al, 2002) are available. Hempel and Bohm (1996) reported that 3-Oglucuronides and 3-O-rutinosides of quercetin and kaempferol were the main flavonoid glycosides in six varieties of yellow and green French beans.…”
Section: Article In Pressmentioning
confidence: 99%